Challenges in Achieving Mastery of the Four English Language Skills: Perspectives from Hospitality Students at SMKN 1 Sukasada - Putu Kevin Aditya; Kadek Sintya Dewi; Gede Mahendrayana (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
This study aims to determine the challenges in achieving competence in four English language skills from the perspective of hospitality students at SMK Negeri 1 Sukasada. The subjects of this study were 13 11th grade hospitality students at SMK Negeri 1 Sukasada. The data obtained were collected through questionnaires and interviews. The results of the study showed that: (1) 11th grade hospitality students have challenges in mastering English speaking and listening (2) difficulties in learning English in hospitality classes (3) data on the scale of English language ability of 11th grade hospitality students at SMK Negeri 1 Sukasada.